Branding Lanang Jarangoyang Banyuwangi Coffee on Instagram @Warkop_Jarangoyang - Kumalasari, Ines; Sinduwiatmo, Kukuh (Procedia of Social Sciences and Humanities, 2024)
This study aims to analyze the branding of Lanang Coffee through Instagram @warkop_jarangoyang. Lanang Coffee has become an important part of rural culture and economy in Kemiren Village, Glagah District, Banyuwangi Regency, Indonesia. Village. This research explores the relationship between brand awareness, brand engagement, and brand loyalty in the context of the technology industry. Using a quantitative approach through observation and in-depth interviews with coffee managers and local consumers. The research found that high brand awareness significantly increases brand engagement, which in turn strengthens brand loyalty. The result of this research is the importance of understanding and supporting local practices such as branding @warkop_jarangoyang using Instagram social media as an integral part of sustainable development in Kemiren Village, Glagah District, Banyuwangi Regency. The practice of branding is also an important economic strategy for farmers to obtain a stable income and improve their welfare. By using digital branding theory and from the results of this study is the importance of understanding and supporting local practices such as branding @warkop_jarangoyang using Instagram social media as an integral part of sustainable development in Kemiren Village, Glagah District, Banyuwangi Regency.